DETERMINATION OF THE ABSOLUTE LINEAR ACCELERATION OF A POINT IN THE WORKING CHAMBER OF THE SPATIAL MECHANISM OF A TUMBLING MACHINE - КОШЕЛЬ, Олександр; ПАНАСЮК, Ігор (Technologies and Engineering, 2025)
Purpose. Determination of the absolute linear acceleration (in magnitude and direction) of a conventional point corresponding to the location of a part in the working chamber of the drum of a tumbling machine for processing light-industry parts, under conditions of complex spatial motion of a cylindrical chamber. Methodology. The kinematic analysis of a point of the working chamber of a machine for processing light-industry parts was carried out using the principles of complex motion of a material point from the course of theoretical mechanics. Findings. Using the principles of theoretical mechanics, the complex spatial motion of a point of the working chamber of the machine was represented as a combination of two simple rotational motions, namely: the relative rotational motion of the point about the geometric axis of the cylindrical chamber, and the transport rotational motion together with the chamber about the geometric axis of two coaxially arranged driving shafts of the machine. Independent investigations of the point acceleration in the relative motion and in the transport motion made it possible to determine the absolute linear acceleration of the selected point of the working chamber in magnitude and direction. Originality. Equations were obtained for calculating the magnitude and direction of the vector of absolute linear acceleration of a conventional point corresponding to the location of a part in the working chamber of a tumbling machine for processing light-industry parts with two independent driving shafts. Practical value. A calculation scheme was developed for investigating the linear acceleration of a point of the working chamber of a tumbling machine for processing light-industry parts under conditions of complex spatial motion of the cylindrical chamber. The calculation scheme allowed independent investigation of the two simple motions resulting from the independent rotational motion of the driving shafts in the relative and transport motion of the working chamber, and made it possible to determine the absolute linear acceleration of the conventional point corresponding to the location of a part in both magnitude and direction. The obtained results of the kinematic analysis enable performing a corresponding assessment of the motion regime of the technological array of parts in the working chamber of the tumbling machine.